O-013 Flow-diverter biological improvement with CD31 biomimetic: preclinical experience. (22nd July 2019) - Cortese, J; Rasser, C; Even, G; Choqueux, C; Bardet, S; Caroff, J; Spelle, L; Caligiuri, G; Rouchaud, A
Abstract : Introduction: The implantation of Flow-Diverter stents (FD) is an effective technic for the treatment of intracranial aneurysms but can expose to severe hemorrhagic and/or ischemic complications due to their metallic structure. CD31 is a trans-membranous protein highly expressed on the luminal surface of arteries and endowed with a contact-driven attractive effect on endothelial cells, and an inhibitory effect of platelets and leucocytes activation. The goal of this study was to evaluate, in vitro and in vivo, whether a coating with P8RI, a biomimetic peptide of CD31, could improve the biocompatibility of FD. Methods: The coating of metal pellets and Silk Vista Baby® (Balt, France) FDs with P8RI was obtained via a series of dip-coating steps, including the formation of an intermediate polydopamine (PDA) layer. In vitro, the adhesion of endothelial cells under different conditions was tested on uncoated and coated metal pellets (PDA alone and PDA with P8RI), and their thrombogenic and inflammatory phenotype were monitored. In vivo, we used a validated elastase-induced saccular carotid aneurysm model in rabbits, separated into three groups: a test group with P8RI-coated FD (P8RI), and two control groups with unmodified FD (UFD) and PDA-coated FD (PDA). Angiographic results were evaluated at 1 and 3 months. Histological, scanning electron and multiphoton microscopy analyses were assessed at 1 month. Patency of covered branches was also evaluated on FD placed in the abdominal aorta covering lumbar arteries. Results: In vitro, P8RI coating promotes adhesion of endothelial cells and induces a less inflammatory and less thrombogenic endothelial cell phenotype. In vivo, 25 aneurysms were created in 25 rabbits and were treated with 7 UFD, 9 PDA and 9 P8RI FDs. There was no significant difference in complete occlusion rate. Histological and microscopy analyses at 1 month showed that the coating with the P8RI peptide improved the integration of the device at the blood vessel interface and the quality of its endothelialization (figure 1). All covered arteries remained patent with no stenosis in all 3 groups. Conclusion: P8RI coating of FD improves biocompatibility and healing process of aneurysm treatment. These results are a crucial step towards a translation to clinical, this technology could be extended also to other intra-arterial devices used in interventional neuroradiology. Disclosures: J. Cortese: 1; C; Fondation pour la Recherche Médicale (DEA20170637766). C. Rasser: None. G. Even: None. C. Choqueux: None. S. Bardet: None. J. Caroff: None. L. Spelle: None. G. Caligiuri: None. A. Rouchaud: None.